2017
DOI: 10.1186/s12933-017-0599-2
|View full text |Cite
|
Sign up to set email alerts
|

High density lipoprotein modulates osteocalcin expression in circulating monocytes: a potential protective mechanism for cardiovascular disease in type 1 diabetes

Abstract: BackgroundCardiovascular disease (CVD) is a major cause of mortality in type 1 diabetes (T1D). A pro-calcific drift of circulating monocytes has been linked to vascular calcification and is marked by the surface expression of osteocalcin (OCN). We studied OCN+ monocytes in a unique population with ≥50 years of T1D, the 50-Year Joslin Medalists (J50M).MethodsCD45 bright/CD14+/OCN+ cells in the circulating mononuclear blood cell fraction were quantified by flow cytometry and reported as percentage of CD45 bright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…34 On the contrary, high levels of HDL cholesterol may prevent nerve damage in diabetes thanks to the well-known anti-inflammatory and anti-oxidative properties of HDL. 19,35 Our data further stress the importance of a multifactorial treatment in people affected by diabetes, 36 which may also result in a decreased risk of cardiac autonomic neuropathy as suggested by clinical trials 37 We did not find differences between participants with and without cardiac autonomic neuropathy in other well-recognized risk factors for diabetes autonomic neuropathy such as glycaemic control, disease duration and eGFR. 9 This finding may be however explained by the overall good glycaemic control, the relatively short mean disease duration and the preserved kidney function of our population.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…34 On the contrary, high levels of HDL cholesterol may prevent nerve damage in diabetes thanks to the well-known anti-inflammatory and anti-oxidative properties of HDL. 19,35 Our data further stress the importance of a multifactorial treatment in people affected by diabetes, 36 which may also result in a decreased risk of cardiac autonomic neuropathy as suggested by clinical trials 37 We did not find differences between participants with and without cardiac autonomic neuropathy in other well-recognized risk factors for diabetes autonomic neuropathy such as glycaemic control, disease duration and eGFR. 9 This finding may be however explained by the overall good glycaemic control, the relatively short mean disease duration and the preserved kidney function of our population.…”
Section: Discussionsupporting
confidence: 59%
“…In this regard, dyslipidaemia has been hypothesized contributing to diabetic neuropathy pathogenesis through several pathways, including increased formation of reactive oxygen species and of oxysterols, activation of the toll‐like receptor and of the advanced glycation end product receptor, all of which mediate local inflammation, causing progressive nerve injury 34 . On the contrary, high levels of HDL cholesterol may prevent nerve damage in diabetes thanks to the well‐known anti‐inflammatory and anti‐oxidative properties of HDL 19,35 . Our data further stress the importance of a multifactorial treatment in people affected by diabetes, 36 which may also result in a decreased risk of cardiac autonomic neuropathy as suggested by clinical trials 37 …”
Section: Discussionsupporting
confidence: 52%
“…The roles of serum OCN and FGF23 levels in regulating energy metabolism have led to new insights into the physiological functions of bone [ 8 , 19 , 20 ]. Maddaloni et al suggested that circulating OCN + monocytes could be a marker for vascular disease in diabetic patients [ 21 ]. Our previous studies found that a decreasing trend in serum OCN levels accompanied an increase in VFA, and VFA was inversely correlated with serum OCN levels [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those studies reporting an association between osteocalcin and CVD risk, only detected an association in elderly (> 70 year); however, these associations were in opposite directions [ 9 , 11 ]. Additionally, one previous study indicated that osteocalcin may be a marker of vascular disease in patients with type 1 diabetes [ 30 ]. Osteonectin was detected in atherosclerotic plaques, but cohort studies focusing on osteonectin and incident CVD risk are lacking, although one study suggested that osteonectin may predict CVD events [ 14 ].…”
Section: Discussionmentioning
confidence: 99%